Synthesis, Characterization, and Preliminary Study of [Co(2- aminopyridine)2(NCS)2] or bis(2-aminopyridine)dithiocyanato cobalt(II) as An Antibacterial - Asmi Munadhiroh; Husni Wahyu Wijaya; Nani Farida; Stéphane Golhen; I Wayan Dasna (Jurnal Kimia Valensi, 2022)
This study aims to synthesize complex compounds from the Co(II) ion with mixed ligands of 2-aminopyridine and thiocyanate ions. The complexes obtained have Co(II) : 2-aminopyridine: thiocyanate ratio of 1:2:2 based on preliminary analysis by SEM-EDX, DHL, and FTIR. The complex in the form of a blue needle crystal is stable at room temperature and melts at 169 °C. Characterization shows that the complex formed is neutral. The antibacterial activity test was carried out using the diffusion method and show that the resulting complex compounds could inhibit the growth of S. typhi and S. aureus bacteria better than 2-aminopyridine.